Service composition with quality of service management in environmental sensor networks. (2016) - Cuong, Nguyen The; Domínguez, Federico; Long, Nguyen Thanh; Touhafi, Abdellah; Steenhaut, Kris
Environmental sensor networks consist of geographically distributed resource-constrained computers that use sensors to measure environmental parameters. They typically collect and distribute environmental data in near real-time using different types of web services. These services are consumed by users and applications that expect appropriate quality of service (QoS) levels. However, acceptable and stable QoS levels are difficult to maintain in environmental sensor networks due to limited computing resources and hostile deployment conditions. We developed a new approach to efficiently manage QoS levels in these networks using two separate tasks: online QoS estimation and QoS-aware service composition. This paper presents our first prototype of a web service composition system that leverages Bayesian classification techniques to perform online QoS estimation by constantly monitoring key environmental and network performance parameters. This system has been tested in a live noise pollution environmental sensor network deployed in the Flanders region in Belgium.